Blancaflor, the hero with secret powers : a folktale from Latin America - Spiegelman, Nadja (TOON graphics., 2021)
Raised by an ogre and a witch, Blancaflor's world is turned upside down when she saves a prince after he falls from the sky. Her father plans to entrap him in an unwinnable game, so Blancaflor promises to use her magical powers to help him escape.